Pengaruh Marketing Mix 7P Terhadap Kepuasan Konsumen Buah Lokal (Studi Kasus di Istana Buah Sultan Agung Semarang) - Tarigan, Junius Imanuel; Mariyono, Joko; Handayani, Migie (Universitas Galuh, 2025)
ABSTRACTThis research aimed to determine the influence of product, price, place, promotion, people, process, and physical evidence on local fruit consumer satisfaction at Istana Buah Sultan Agung. The method used in this research was quantitative with case studies. The choice of research location was carried out purposively with the consideration that Istana Buah Sultan Agung was one of the largest fruit shops in the city of Semarang. The data source in this research was primary data originating from the sample, namely visitors to the Istana Buah. Data collection was carried out using interview techniques by distributing questionnaires to 160 respondents. The data analysis used in this research was multiple linear regression analysis. The results of this research showed that the variables 1) product had no significant effect on consumer satisfaction, 2) price had no significant effect on consumer satisfaction, 3) place had a significant effect on consumer satisfaction, 4) promotion had no significant effect on consumer satisfaction, 5) people had a significant effect on consumer satisfaction, 6) process had no significant effect on consumer satisfaction, 7) physical evidence had no significant effect on consumer satisfaction, 8) place and people variables partially influenced customer satisfaction at Istana Buah Sultan Agung, Semarang City.